2010
DOI: 10.2175/106143009x426013
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hexavalent Chromium in Aqueous Medium with Zerovalent Iron

Abstract: Hexavalent chromium, emanating primarily from the tannery and electroplating industries, can be reduced to the less toxic trivalent variety by several methods, including reduction with metallic iron. In the present work, electrolytic-grade iron dust was used to reduce chromium(VI) in the form of potassium dichromate. Loading of iron dust was varied from 0.5 to 1.0 g in 50 mL of solution; the pH of the medium was varied from 1.5 to 3.5; and the initial concentration of the dichromate solution was varied from 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
(37 reference statements)
1
15
0
2
Order By: Relevance
“…The reduction of Cr(VI) by ZVI is highly sensitive to the solution pH, as reported by numerous studies, the reduction rates increasing as the pH decreases (Alidokht et al 2011;Bowers et al 1986;Dutta et al 2010;Geng et al 2009b;Gould 1982;Ozer et al 1997;Powell and Puls 1997;Qian et al 2008;Weng et al 2007;Wu et al 2009). This is in accord with the stoichiometry of this reaction (Eq.…”
Section: Effect Of Phmentioning
confidence: 89%
See 1 more Smart Citation
“…The reduction of Cr(VI) by ZVI is highly sensitive to the solution pH, as reported by numerous studies, the reduction rates increasing as the pH decreases (Alidokht et al 2011;Bowers et al 1986;Dutta et al 2010;Geng et al 2009b;Gould 1982;Ozer et al 1997;Powell and Puls 1997;Qian et al 2008;Weng et al 2007;Wu et al 2009). This is in accord with the stoichiometry of this reaction (Eq.…”
Section: Effect Of Phmentioning
confidence: 89%
“…Additionally, sorption of negatively charged Cr(VI) oxyanions onto ZVI is preferred at low pH because the ZVI surface is more positively charged . Under strong acidic conditions, Cr(VI) reduction was reported to be very fast Dutta et al 2010;Gheju and Iovi 2006), even instantaneous at pH 1 ). However, Chen et al (2007) observed that at pH 1, ZVI had a reduced lifetime than at pH 1.5, which was attributed to a higher reactivity of ZVI towards hydrogen ions at pH 1; consequently, optimum pH was shown at pH 1.5 instead of pH 1 .…”
Section: Effect Of Phmentioning
confidence: 99%
“…Unfortunately, these reports co-exist in the literature with publications demonstrating that Fe 0 surface is universally covered by oxide layers [61][62][63][64][65][66], and that Fe 0 is additionally passivated with corrosion products during the remediation process [44,52,61,67,68]. Numerous recent studies, aimed to gain insight into the principles governing the removal of Cr VI in Fe 0 /H 2 O systems, have also presumed that this process is exclusively the result of direct electron transfer from Fe 0 to Cr VI [69][70][71][72][73][74][75][76][77][78][79]. Since the surface of commercially Fe 0 materials is permanently covered by an outer layer of low electric conductive air-formed oxides (hematite, maghemite) [64], the electron transport from Fe 0 to Cr VI should be severely inhibited [69][70][71][72][73][74][75][76][77][78][79].…”
Section: More Recent Laboratory-scale Reports (Post Elisabeth City Prb)mentioning
confidence: 99%
“…Numerous recent studies, aimed to gain insight into the principles governing the removal of Cr VI in Fe 0 /H 2 O systems, have also presumed that this process is exclusively the result of direct electron transfer from Fe 0 to Cr VI [69][70][71][72][73][74][75][76][77][78][79]. Since the surface of commercially Fe 0 materials is permanently covered by an outer layer of low electric conductive air-formed oxides (hematite, maghemite) [64], the electron transport from Fe 0 to Cr VI should be severely inhibited [69][70][71][72][73][74][75][76][77][78][79]. Moreover, Fe 0 efficiency should significantly decrease during the time, as its surface is progressively covered with additional secondary mineral coatings that prevents penetration of the Cr VI and stops the electron transfer [11,[80][81][82].…”
Section: More Recent Laboratory-scale Reports (Post Elisabeth City Prb)mentioning
confidence: 99%
“…There we had reported different aspects of the batch reaction with ZVI in the form of iron dust and potassium dichromate solution (Dutta et al 2010). In case of steel wool, iron filings or scrap iron, it is difficult to determine the geometry or surface area of such irregular-shaped reductant accurately, and therefore it is nearly impossible to propose any rate model for the surface-reduction process since the rate equation explicitly contains transient active surface area.…”
Section: Introductionmentioning
confidence: 99%